Protein secretion by enteropathogenic Escherichia coli is essential for transducing signals to epithelial cells. - Kenny, B (1995)
Enteropathogenic Escherichia coli (EPEC), a major cause of pediatric diarrhea, adheres to epithelial cells and activates host cell signal transduction pathways. We have identified five proteins that are secreted by EPEC and show that this secretion process is critical for triggering signal transduction events in epithelial cells. Protein secretion occurs via two pathways: one secretes a 110-kDa protein and the other mediates export of the four remaining proteins. Secretion of all five proteins was regulated by temperature and the perA locus, two factors which regulate expression of other known EPEC virulence factors. Amino-terminal sequence analysis of the secreted polypeptides identified one protein (37 kDa) as the product of the eaeB gene, a genetic locus previously shown to be necessary for signal transduction. A second protein (39 kDa) showed significant homology with glyceraldehyde-3-phosphate dehydrogenase, while the other three proteins (110, 40, and 25 kDa) were unique. The secreted proteins associated with epithelial cells, and EaeB became resistant to protease digestion upon association, suggesting that intimate interactions are required for transducing signals.